The Learning Styles of Nursing Technicians Students and their Usefulness in Teaching Didactics - Zúñiga González, Mónica (2023)
The objective of this paper is to identify the learning styles of first-year students of the higher-level Nursing Technicians career in order to discuss their importance and usefulness in the didactic dimension of personal teaching practice. The authors carried out a statistical analysis with a trend of the variables, this through a quantitative orientation and observational, descriptive, cross-sectional scope, carried out with a sample of 72 students from three successive cohorts (2017 to 2019) and through the application of the V.A.K. (visual, auditory, kinesthetic). The results show the predominance in the learning styles of the different cohorts. Moreover, the discussions revolve around the need and usefulness of knowing learning styles and how this evidence allows to optimize the teaching and learning processes. It is concluded that each cohort has a more predominant learning style; for example, in 2017 and 2018 the visual style stood out, but in 2019 the kinesthetic was predominant. The latter is related to the career profile. Therefore, it is recommended that teachers know the student’s learning style in order to use active methodologies in the classroom and achieve user satisfaction, as well as better academic performance.